The structural basis for how the large ribosomal subunit catalyses peptide bond formation - Steitz, Thomas (Henry Stewart Talks, 2008)
Overview of protein synthesis by the ribosome, Nature of the polypeptide exit tunnel in the large subunit, The ribosome is a ribozyme, Substrate induced fit at the peptidyl transferase center, Proton shuttle mechanism and transition state stabilization, Substrate interactions at the large subunit E-site, Movie of the peptidyl transferase reaction